Development of Engineering Mechanics Module as Student's Learning Material In Google Classroom - Ikhwan, Syaiful; Syah, Nurhasan; Giatman, M.; Ambiyar, Ambiyar (STAI Miftahul Ula Nganjuk, 2021)
In the Mechanical Engineering subject the teacher has compiled a module but the module has not been developed properly, the content of the module only contains a collection of learning materials that do not meet the basic competency standards that must be mastered by students in the syllabus. Weaknesses in the previous module were not equipped with instructions for using the module, learning evaluation, answer keys and bibliography which were made in a systematic and structured manner as the module should be. So that if the engineering mechanics module has been developed, it can be used as a good teaching material used by students both during face-to-face and online learning. Especially for online learning, modules that have been developed are needed to be used as teaching materials for students in Google Classroom so that students can access them at any time and learn independently. The module development research procedure uses a modified 4-D models development model. The development model consists of four stages, namely Define (defining), Design (design), Develop (development) and Disseminate (dissemination) but at the disseminate stage (dissemination) is carried out in a limited way, namely only to class X students, Department of Modeling and Building Information Design at SMK N 1 Padang which is the subject of product trials. The results obtained from this development research are as follows: (1) Engineering Mechanics learning module, (2) The validity of the learning module is declared valid on the content aspect with a value of 0.93 > 0.67, the format aspect is obtained a value of 0.85> 0.67, (3) The practicality of the learning module, based on the teacher's response, was stated to be very practical with an average value of 92.30 and based on 36 student responses stated to be practical, an average value of 76.50 was obtained, (4) The engineering mechanics learning module, was declared effective. improving aspects of student knowledge can be seen from improving student learning outcomes and effectively improving aspects of student skills seen from the results of the resulting picture assignments. Based on the results of this study, it can be concluded that the Engineering Mechanics learning module has been valid, practical and effective as a learning resource in Engineering Mechanics subjects.